Winter sighting of a known western North Atlantic right whale in the Azores - Silva , Monica A.; Steiner , Lisa; Cascao, Irma; Cruz, Maria Joao; Prieto, Rui; Cole, Tim; Hamilton, Philip K.; Baumgartner, Mark (J. Cetacean Res. Manage., 2023)
A right whale (Eubalaena glacialis) from the western North Atlantic population, sighted in the Azores, was subsequently found to have moved back to the northwest Atlantic. The whale was sighted in the Azores on 5 January 2009 travelling in a west-south westerly direction at a constant speed. A photographic match was found to an adult female in the North Atlantic Right Whale Catalogue. The whale’s previous last sighting, on 24 September 2008 in the Bay of Fundy, Canada, implies movement to the Azores of at least 3,320km in 101 days. It was subsequently resighted in the Bay of Fundy on 2 September 2009, 237 days after being seen in the Azores. This appears to be the only documented evidence of a western North Atlantic right whale outside its normal range in winter, and provides additional evidence of the potential for interbreeding between western North Atlantic right whales and the remnant eastern population.